NEOLIBERALISM AND FOREIGN POLICY: INTERDEPENDENCY AND INTERCONDITIONALITY IN THE CONTEXT OF INTEGRATION PROJECTS IN UKRAINE - Новіков, М.М. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 2013)
Interdependency and interconditionality of domestic and foreign policy of contemporary Ukraine and influence on formation the main postulates of neoliberalism are examined. It is given the arguments for alternative projects of integration (European Union and Customs Union), to interpret some reasons of its slow realization.